A remarkable new species and one newly recorded species of genus Oxyartes Stål, 1875 (Phasmida, Lonchodidae, Necrosciinae) from China - Gao, Hao-Ran; Wang, Chen; Zhang, Hong-Rui (Zootaxa, 2024)
The genus Oxyartes currently comprises 17 taxa, of which 12 are found in China, representing the high diversity in China. This list includes the two species from China as described in this paper. The first is a new remarkable species O. bouxraeuz sp. nov. collected from Gulinqing township, Yunnan. The second is a newly recorded species, O. cresphontes. This species is reported from Mêdog, Xizang, China. A key to this genus from China is presented. Type specimens are deposited in the Yunnan Agricultural University (YNAU).